The role of innovation and entrepreneurship in economic growth - Chatterji, Aaron, 1978-; Lerner, Josh, 1978-; Stern, Scott; Andrews, Michael J. (National Bureau of Economic Research conference report., 2022)
This volume presents studies from experts in twelve industries, providing insights into the future role of innovation and entrepreneurship in driving economic growth across sectors. We live in an era in which innovation and entrepreneurship seem ubiquitous, particularly in regions like Silicon Valley, Boston, and the Research Triangle Park. But many metrics of economic growth, such as productivity growth and business dynamism, have been at best modest in recent years. The resolution of this apparent paradox is dramatic heterogeneity across sectors, with some industries seeing robust innovation and entrepreneurship and others seeing stagnation. By construction, the impact of innovation and entrepreneurship on overall economic performance is the cumulative impact of their effects on individual sectors. Understanding the potential for growth in the aggregate economy depends, therefore, on understanding the sector-by-sector potential for growth. This insight motivates the twelve studies of different sectors that are presented in this volume. Each study identifies specific productivity improvements enabled by innovation and entrepreneurship, for example as a result of new production technologies, increased competition, or new organizational forms. These twelve studies, along with three synthetic chapters, provide new insights on the sectoral patterns and concentration of the contributions of innovation and entrepreneurship to economic growth.